DETERMINATION OF TRANSMISSION GEAR RATIO IN MECHANICAL PART OF TRACTOR ELECTRO-MECHANICAL TRANSMISSION - Ch. I. Zhdanovich; N. V. Kalinin (Наука и техника)
A methodology has been developed for selection of gear number and transmission gear ratios in mechanical part of a wheel-type tractor with electro-mechanical transmission containing a propulsion asynchronous electric motor with variablefrequency control. The paper proposes to determine a transmission gear ratio on the basis of the following: provision of wheel torque dependence on tractor speed which is the best one for a traction process and during transfer from one gear to the other; provision of nominal operational mode of the electric motor for all tractor operations where it is working for a long period of time; provision of minimum possible number of gears; complete realization of internal combustion engine power on the tractor wheels at limit operational mode of the electric motor. As a characteristic of the asynchronous electric motor with variable-frequency control contains various portions which can be used either completely or partially due to operating conditions, the gear number is determined in the process of transmission gear ration finding but not prior to this. A wheel torque of the tractor with electro-mechanical transmission can be limited according to the following factors: grip of wheel with supporting surface; maximum power of an internal combustion engine which can be transferred to the wheels and a torque which is developed by a propulsion electric motor. It is not proposed to exceed nominal operational mode of the propulsion electric motor for all the operations of the tractor if it is working for a long period of time because in the case of significant excess of the nominal operational mode of the asynchronous electric motor its rather long operation leads to low efficiency and high losses in power, large heat liberation and consequently requires to develop more complicated system for electric motor cooling. An excess of nominal electric motor torque can be justified for short-term operational modes because in this case there is no need to select more powerful electric motor and create an additional gear in the gear-box.